Little black dress - Talley, André Leon 1949-2022 (Skira Rizzoli, 2012)
"A celebratory tribute to the iconic little black dress and its deeply resonant cultural and social significance in the modern era ... Features an impeccable group of more than 80 dresses from many of the most eminent fashion houses"...Jacket